The Effect of the Undistributed Profits Tax upon the Distribution of Corporate Earnings: A Note - Guthmann, Harry G. (Econometrica, 1940)
ON READING Mr. McIntyre's article' on the undistributed profits tax one is chiefly impressed not that he reaches the conclusion that the tax has no appreciable effect on dividend distributions but that his chart apparently indicates that the tax actually had the effect of causing a distribution that was very much below normal. His scatter-chart showing the ratio of dividends to earnings on the vertical scale and the per cent of industrial activity to on the horizontal scale shows a negative relationship as would be expected. But the two data for 1936 and 1937, the two years during which the tax was in effect, while showing a relatively high distribution compared with the mass of data, are considerably below and to the left of this main island of cases. The impression conveyed to the reader is that the dividend distributions of 1936 and 1937 were really quite low when read in the light of industrial activity. Thus it appears that the undistributed profits tax has the effect of causing retention rather than distribution of earnings. A possible explanation of this extraordinary result would lie in the definition of normal industrial activity for the years 1936 and 1937. As in most indexes of normality weighted heavily with the tendencies established in the 1920's there may well be a considerable overstatement of the normal trend line. The data which will establish current normality lie in the future and so are indeterminate. The final data for any trend or normal series are the most uncertain and the whole significance of the chart used in this article depends upon the accuracy of this normal for the last two years, 1936 and 1937. If a lower normal for industrial activity were established, the present position of the dividends-to-earnings ratios would move to the right and so alter the picture at its crucial point. A simpler and clearer picture is obtained by merely charting the Cowles indexes of earnings and dividends. Reference to the accompanying chart, Figure 1, showing these figures, leads one to the conclusion that the proportions of earnings distributed in 1936 and 1937 were comparatively high. Of the years in which dividends were less than earnings (and so bore a substantial relation to that year's earnings) only eight years showed a higher per cent than 1936 and 1937, three were within the range of the 1936 and 1937 data (74.4 per cent and 78.7 per cent), and forty-seven were lower.